Periprosthetic Atypical Femoral Fractures in Patients on Long-term Bisphosphonates: A Multicenter Retrospective Review. Issue 4 (April 2016) - Robinson, Juan de Dios; Leighton, Ross K.; Trask, Kelly; Bogdan, Yelena; Tornetta, Paul
Abstract : Objectives: To define the characteristics of periprosthetic atypical femoral fractures (PAFFs) in patients on long-term bisphosphonate treatment and to provide a guide to the diagnosis and long-term treatment of these patients based on the literature. Design: Multicenter retrospective review. Setting: Fifteen orthopaedic centers in the United States and Canada, including members of the Canadian Orthopaedic Trauma Society. Patients/Participants: Patients on long-term bisphosphonates who presented with either periprosthetic fractures or femoral fractures, over a 10-year period. Main Outcome Measurements: Time to union and complications. Results: Clinically significant differences were identified in time to union, mortality, and complications. There was a statistically significant difference in complications. Imaging review demonstrated identical features in both atypical femoral fractures (AFFs) and PAFFs. Conclusions: This is the largest comparative case series reported on PAFFS and AFFs and provides compelling evidence that PAFFs in patients on long-term bisphosphonates are indeed a subset of periprosthetic fractures that exhibit atypical femoral fracture (AFF) characteristics. As such, these fractures pose serious diagnostic and management challenges to trauma and arthroplasty surgeons. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.